THU0042 Preclinical Characterization of Sirukumab, a Human Monoclonal Antibody that Targets Human Interleukin-6 Signaling. (9th June 2015) - Gardner, D.; Lacy, E.; Wu, S.; Shealy, D.
Abstract : Background: A significant fraction of patients with rheumatoid arthritis (RA) have an inadequate response to tumor necrosis factor α inhibitors as well as to biologics that target other pathways, such as anti-CD20 (rituximab), CTLA4-Ig (abatacept), or anti–interleukin-6 (IL-6) receptor (tocilizumab; TCZ). Due to the high concentrations of soluble IL-6 receptor (IL-6R) found in the blood and synovial fluid of patients with RA, we elected to examine whether targeting the cytokine IL-6 rather than IL-6R is a more efficient means to inhibit IL-6 signaling. Objectives: To characterize sirukumab (SIR), a monoclonal human IgG1κ antibody specific for human IL-6, and compare neutralization of IL-6 signaling with TCZ, which targets the soluble and membrane forms of IL-6R. Methods: Affinity and selectivity for human IL-6 were determined using kinetic exclusion, in vitro binding, and 7TD1 cell proliferation assays. The epitope recognized by SIR on human IL-6 was determined by protease protection and solution hydrogen-deuterium exchange, which was confirmed by alanine substitution. In vitro bioassays were used to demonstrate inhibition of IL-6 signaling and compare potency with TCZ. BALB/c mice challenged with human IL-6 produce serum amyloid A; this model was used to examine the potency of SIR in vivo. Results: SIR bound to human IL-6 with high affinity (0.175 pM). Epitope mapping identified helix D, spatially proximal regions of helix A, and the loop before helix B as the binding sites for SIR on IL-6. These overlap with the site where soluble IL-6R binds to IL-6. SIR showed no binding of human IL-6 bound to the IL-6R/gp130 receptor complex on U937 cells. SIR did not recognize other ligands that signal through gp130, and species crossreactivity to IL-6 was limited to human and nonhuman primates. SIR, at doses of 5 and 0.5 mg/kg, significantly reduced expression of serum amyloid A in BALB/c mice challenged with human IL-6 compared to mice that received an isotype-matched, negative control antibody ( P <0.05). In several bioassays utilizing U937, HepG2, and human endothelial cells, SIR ranged from 50-fold to 90-fold more potent than TCZ. Conclusions: Current data suggests that SIR binds with high affinity and neutralizes the biological effects of human IL-6. In side-by-side bioassays, SIR appears to be more potent than TCZ. Phase 3 clinical trials are underway to establish the efficacy and safety of SIR in patients with RA. Acknowledgements: Study sponsored by Janssen Research & Development, LLC, in collaboration with GlaxoSmithKline. Disclosure of Interest: D. Gardner Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC, E. Lacy Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC, S. Wu Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC, D. Shealy Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC